Health-Related Behaviours of Tertiary Education Students: Findings from a New Zealand Study - Humphrey, Richard; Ditzel, Dr Liz; Terry, Stuart (International Journal of Innovative Research in Medical Science, 2017)
This study assessed the prevalence of five health-related behaviours (engagement with health providers, physical activity, diet, alcohol consumption, and smoking) among a population of tertiary students. The findings were used to inform the institution’s ongoing development of health education strategies and the paper concludes with a number of recommendations for others wishing to embed health education and promotion their campus culture.